Infinite-dimensional vector optimization and a separation theorem. (1st December 2020) - Amahroq, Tijani; Oussarhan, Abdessamad
ABSTRACT: Using relative minimality solutions for vector optimization problems, we establish optimality conditions in terms of Karush–Kuhn–Tucker multipliers as well as Fritz-John multipliers. Moreover, we give a general separation theorem including both finite and infinite classical separation theorem.